Pengaruh Variasi Udara Pembakaran Terhadap Efisiensi Boiler dengan Menggunakan Perhitungan Metode Langasung dan Tidak Langsung - Restu Dwi Ari Zulfikar; Budi Suharto; Indriyani, Indriyani (SURYA TEKNIKA, 2024)
Boiler type DG1025/17.4 – II 13 Dong Fang Boiler Group Co., Ltd. is a type of boiler is a type of boiler in PLTU Banten 3 Lontar. Boiler efficiency in the steam generation process is influenced by various factors, the most significant of which is how the combustion process occurs in the combustion process occurs in the furnace. Perfect combustin definitely requires a combination of the rught ratio of combustion air and fuel. Based on the result of this researh, it appears that if the actual amount of air flow required for the combustion process is 6.15 kg air/kg coal, then the theoritical air requirements is known to be 8.35 kg air/kg coal. This means that if the actual amount of air flow required for the process is close to the theoritical air flow value, it will indirectly increase the boiler combustion efficiency value. It is proven that when the combustion air variation is the smallest, namely 1050 T/h, it produces a boiler efficiency of 66.82% (direct), then at the largest combustion air variation, namely 1200T/h, it produces an efficiency of 72.40% (direct).